Oncoplastic breast-conserving surgery: More relevant than ever? Results of a survey among breast surgeons - Heil, Joerg; Riedel, Fabian; Solbach, Christine; Gerber, Bernd; Marx, Mario; Brucker, Sara; Heitmann, Christoph; Hoffmann, Juergen; Wallwiener, Markus; Lux, Michael P.; Wallwiener, Diethelm; Hahn, Markus (Archives of Gynecology and Obstetrics, 2019)
PurposeOncoplastic breast-conserving surgery has been part of clinical routine for several years without an internationally accepted nomenclature, standardization or a systematic evaluation of single surgical procedures.MethodsWe carried out a structured survey of breast surgeons (n=50) during the annual meeting of the German Society for Senology in Berlin 2017. In the run-up to the event, 10 questions were determined and released for an anonymous survey during the consensus meeting.ResultsMost surgeons participating in the consensus meeting had an expertise of more than 200 oncologic breast surgeries in the last 3years and approved the need of a higher rate of standardization in oncoplastic techniques. From the oncological standpoint, oncoplastic surgery is considered safe with a comparable rate of compilations as seen in conventional breast-conserving procedures. Most surgeons approve that using oncoplastic surgery, higher rates of breast conservation and improved aesthetic results can be accomplished. The majority of the participants would endorse a more systematic review of subjective aesthetic results in clinical routine.ConclusionsA higher degree in standardization of oncoplastic breast surgery is required for surgical-technical, educational, and scientific reasons as well as for a more differentiated monetary compensation of the surgical procedures. This process has already been started.
CRIS-Team WoS Importer:2019-04-12